Designing an augmented reality in-car driving simulator / Haryati Fauzi ... [et al.] - Fauzi, Haryati; Osman, Aznoora; Hashim, Muhamad Arif; Ahmad Baharin, Ahmad Hanif (UiTM Cawangan Perlis, 2016)
This paper demonstrates the design of augmented reality (AR) in-car driving simulator system architecture and its experimental design. AR in-car driving simulator is developed in order to explore its effect towards subjects' simulator sickness when operating the driving simulator. Sensory conflict theory postulates that simulator sickness is a condition where an information between vestibular input system and visual that provides orientation and movement information is misaligned. Simulator sickness is a well-known issue entangled with simulator and various past research revealed that some of the methods to avoid simulator sickness are by taking prescribed medicine, shortening the length of drives and adjusting light of driving simulation environment. Augmented reality allows a combination between real world views with computer-generated object and runs in a real-time performance. By using AR, it is possible to create an outdoor driving simulator that allows a real world view with a mixture of case study that been replicate by computer. Affording similar driving experience to driving a normal car, AR is believed to be an alternative solution to simulator sickness. Therefore, the AR driving simulator would be employed in experimental study to measure its effect on simulator sickness towards subjects.